(untitled) (Global Journal of Human-Social Science, 2012)
This paper offers an analysis of changing expectations of the husbands from their wives in Haryana state of India This paper explores the alterations in gender relationship pattern in the Haryana region that has experienced major socio-political and economic changes in the last two decades Positional survey research design was used for the present study through interview schedule comprising open ended questions Husbands from different socio-economic background reported the continuing influence of traditional values that still govern the gender relationships in the family particularly husband-wife relationship